Exploring consumers’ perception of farm animal welfare in Muar, Johor - Nalini Arumugam; Ain Shafirah Mohd Halim; Anath Rau Krishnan (International Journal of Scientific Research and Management, 2024)
The concept of animal welfare has been in existence since the early 1950s, and the Animal Welfare Act of Malaysia was officially established in 2015. Farm animal welfare (FAW) pertains to the imperative for farmers to establish habitats that enable animals to manifest their innate behaviors. Consumer perception encompasses the way individuals perceive various aspects of animal welfare, including variations in perception among species and nations, the impact of animal-friendly branding, and the extent to which consumers are ready to pay more for food produced from animals maintained under improved welfare conditions. In Malaysia, customers exhibit limited concern for farm animal welfare and possess insufficient awareness regarding the treatment of animals bred for food. The objective of this study was to establish the correlation between customers' impressions of farm animal welfare and their attitudes, knowledge, preferences for welfare-friendly products, and socio-demographic factors. This study categorized attitude, knowledge, welfare-friendly items, and socio-demographic parameters as independent variables, while customers' perception was considered the dependent variable. This study employed a simple random sampling method, selecting 100 participants in Muar, Johor. Data was gathered by distributing a survey questionnaire to consumers in Muar, Johor. The data is analyzed using SPSS, which provides outputs for descriptive and regression analyses. The results indicated that consumers' evaluations of farm animal care were highly influenced by their attitudes and level of knowledge. The findings indicated that residents in Muar, Johor lack awareness and knowledge concerning the well-being of livestock. Hence, it was imperative for consumers and students to grasp the concept of farm animal welfare in order to understand the manner in which animals were handled for the purpose of food production